IMPLEMENTASI MODUL AJAR MAN JADDA WAJADA DALAM PEMBELAJARAN BAHASA ARAB KELAS V DI MI MA’ARIF NU KLESMAN WONOSOBO - Latifah Nur Azizah; Fatkhurrohman; Rifqi Aulia Rahman (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to explore the implementation of the Man Jadda Wajada teaching module in Arabic language instruction at MI Ma’arif NU Klesman, Wonosobo, and to assess its impact on the comprehension of fifth-grade students. This inquiry is significant because Arabic holds a strategic position as a religious language and as a vehicle for understanding the Qur’an. Effective instruction requires learning materials that align with learners’ characteristics, and an interactive module is expected to boost both student engagement and learning outcomes. A qualitative field research approach was employed. Data were gathered through direct classroom observations, in-depth interviews with teachers and students, and documentation of instructional materials and student work. Data analysis followed three stages: data reduction to extract relevant information, data presentation in descriptive narrative form, and drawing conclusions based on field findings. Findings indicate that each lesson begins with singing the Man Jadda Wajada memorization song, followed by a review of previous material via question-and-answer and introduction of mufrodat (vocabulary) by the teacher. New content is delivered through vocabulary recitation, which students then imitate. Singing the mufrodat aids memorization, after which students collaboratively translate the vocabulary. Each session concludes with reflection, assignment of homework, and motivational encouragement for independent study. The module’s successful implementation was supported by students’ enthusiasm for learning, engaging teaching methods, peer support, and strong collaboration among teachers, students, and the school. Challenges included varying levels of motivation, differences in students’ abilities, and less-than-ideal classroom conditions. Proposed strategies to address these barriers include providing supplementary instruction, improving classroom management, and leveraging faster learners to assist peers. Evaluation techniques comprised written tests, oral assessments, and end-of-semester evaluations. Written tests reinforced conceptual understanding, oral assessments honed speaking skills, and the final evaluation measured overall learning achievement. Results showed that all students passed, with an average score of 93.31—categorized as “very good”—demonstrating that the Man Jadda Wajada module effectively enhanced fifth graders’ Arabic comprehension and contributed positively to the overall learning process.